Focal impairment in myocardial fatty acid imaging in the left anterior descending artery area, a strong predictor for cardiac death in hemodialysis patients without obstructive coronary artery disease - Nishimura, Masato (Eur J Nucl Med Mol Imaging, 2015)
PURPOSE: We investigated whether impaired patterns of myocardial fatty acid imaging were associated with cardiac death in dialysis patients without coronary lesions. METHODS: We prospectively enrolled 155 hemodialysis patients without obstructive coronary artery disease, who had been examined by single-photon emission computed tomography (SPECT) using the iodinated fatty acid analogue BMIPP. Uptake of BMIPP on SPECT was graded in 17 segments on a five-point scale (0, normal; 4, absent) and assessed as BMIPP summed scores. Of the enrolled 155 participants, we analyzed 95 who had BMIPP summed scores ≥ 6 (52 men and 43 women, 65 ± 11 years). BMIPP scores ≥ 2 in ≥ 2 consecutive segments in SPECT were defined as focal, and the others as non-focal pattern. RESULTS: Of 95 participants analyzed, 42 (44.2 %) showed focal and 53 (55.8 %) non-focal type. During follow-up for 5.1 ± 2.0 years, 42 died of cardiac events. The occurrence of cardiac death was higher in the focal than in the non-focal group (30/42 [71.4 %] versus 12/53 [22.6 %], p = 0.001). In stepwise Cox hazard analysis, focal pattern was associated with cardiac death (hazard ratio 2.266), independent of impairment of BMIPP SPECT (BMIPP summed scores ≥ 12). The predictive potential of BMIPP SPECT for cardiac death was higher (p < 0.001) in the left anterior descending artery area compared with other coronary territories. CONCLUSIONS: Focal impairment in myocardial fatty acid imaging in the left anterior descending area may strongly predict cardiac death in this population.